Peran Pendidikan Kewarganegaraan dalam Membina Sikap Toleransi antar Siswa di Sekolah. - Siti Rahma; Syamzaimar Syamzaimar (Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2026)
This research used a qualitative approach with a descriptive analytical research type through a literature study method. The research data were obtained from various written sources such as scientific journals, books, research articles, and other documents relevant to the research topic. Data collection techniques were carried out through documentation by reading, recording, and classifying data according to the focus of the research. Data analysis was conducted descriptively and qualitatively through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that Civic Education has an important role in instilling tolerance values in students through materials related to diversity, democracy, human rights, and Pancasila values. Civic Education learning helps students understand the importance of respecting differences in ethnicity, religion, culture, and opinions in everyday life. In addition, teachers also play an important role in fostering tolerance through group discussions, teamwork, and presentation activities that train students to respect and cooperate with one another. However, there are still obstacles in implementing tolerant attitudes, such as environmental influences and the lack of awareness among some students. Therefore, cooperation between teachers, schools, and parents is needed to continuously foster students’ attitudes of tolerance.